Análisis del sistema de alumbrado público, para la presentación de una propuesta de telegestión en los parques, Juan Montalvo y Pedro Fermín Cevallos de la ciudad de Ambato, provincia de Tungurahua, año 2015 - Masaquiza Masaquiza, Christian (2016)
This present project aims to control and remote monitoring of the network of street lighting in, Juan Montalvo and Pedro Fermin Cevallos parks and in Antonio Jose de Sucre street in Ambato city, offering a complete solution to all the problems of overconsumption, pollution and maintenance; as a result of the existing manual control systems. First an analysis of the current situation of the street lighting system, was done for which measurements on the circuits which energize each one of the study sites were performed, and in this manner real data consumption of energy in the lighting system was obtained. Secondly based on the data collected, the evaluation of them were done, having as comparison parameters the current regulations as CONELEC-ARCONEL 005/14 regulation, and the recommendations made for that company….